2018
DOI: 10.1155/2018/5756180
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Vibration of Ladle Crane due to a Moving Trolley

Abstract: The structural vibration of the main beam of a crane causes fatigue damage and discomfort to the driver. The swing of the payload has an effect on positioning precision, especially for a ladle crane, and this directly affects production safety. To study the influence of system parameters on the vibration of a crane's main beam and the angle of the payload, a system consisting of the main beam, trolley, payload, and cabin was constructed. A rigid-flexible coupling dynamic model of a moving trolley with a hangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…As can be seen from Figure 3, the two calculation results were consistent with the underlying trend. A close match can also be observed between the results shown in Case 2 [30] and the model developed in this paper. Since the deviations between the three curves are quite small, the formulations and computer programs developed in this paper should be acceptable methods of calculating the dynamic responses of a beam when subjected to a moving trolley.…”
Section: Deflection Of the Beam When Subjected To A Movingsupporting
confidence: 85%
See 2 more Smart Citations
“…As can be seen from Figure 3, the two calculation results were consistent with the underlying trend. A close match can also be observed between the results shown in Case 2 [30] and the model developed in this paper. Since the deviations between the three curves are quite small, the formulations and computer programs developed in this paper should be acceptable methods of calculating the dynamic responses of a beam when subjected to a moving trolley.…”
Section: Deflection Of the Beam When Subjected To A Movingsupporting
confidence: 85%
“…e length of the beam was L � 10 m and the cross-sectional area was A � 9 × 10 −4 m 2 , and the second moment of area was I � 1.04 × 10 −6 m 4 . e above parameters for the beam were the same as in references [29,30]. Figure 3 shows the graphical time histories for the vertical central deflections of the simply supported beam.…”
Section: Deflection Of the Beam When Subjected To A Movingmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing crane models do not take into account the mass m p and swing angle θ x of the payload; thus, without considering factors such as cab weight, connection mode, and installation position, the existing mathematical model cannot replicate the actual working conditions of the crane. erefore, a physical model that more closely simulates the actual working conditions of the crane ( Figure 6) is proposed [29]. According to the crane system dynamics model during the operation of trolley shown in Figure 6, the forces on the system mainly include the gravity loads, inertial force, structural elastic force, and dissipative force of each component.…”
Section: Crane Dynamic Model Considering Cabin Factorsmentioning
confidence: 99%
“…Many researchers used the assumed mode method to establish the dynamic model of overhead crane systems [2][3][4][5] and quayside container crane systems [6]. It is found that the value of the beam deflection increases by increasing the total mass of the trolley and payload [2][3][4]. In [2], the authors also found that, for given masses of the trolley and payload, the location and the value of the maximum beam deflection are dependent upon the trolley speed.…”
Section: Introductionmentioning
confidence: 99%